The relationship between external and internal load, sleep, and wellness during an off-season phase in women's collegiate NCAA Division I lacrosse athletes - Sutton, P. J.; Cintineo, H. P.; Mumford, P. W.; Sunderland, K. L. (The Journal of Strength and Conditioning Research, 2025)
The purpose of this study was to investigate the bidirectional associations between workload, recovery, sleep, and wellness during the off-season in collegiate women's lacrosse athletes. Data from 20 athletes were evaluated throughout 2 weeks of off-season. Workload was determined by Edwards Training Impulse (eTRIMP), total distance (TD), high-speed running distance (HSR), and session rating of perceived exertion-derived internal training load (sRPE-TL). Resting heart rate and heart rate variability were measured during a 10-minute period upon waking each morning. A Consensus Sleep Diary and Modified Hooper wellness questionnaires were completed within 60 minutes of waking to determine sleep efficiency (SE), sleep onset latency, wake after sleep onset (WASO), total sleep time, and wellness scores. Repeated-measures correlations determined the bidirectional relationships between workload and measures of sleep and wellness (a = 0.05). Total distance, eTRIMP, and sRPE-TL inversely correlated with the following night's SE (r = -0.204, -0.218, and -0.172, respectively) and SE positively correlated with same-day TD (r = 0.222) and eTRIMP (r = 0.199). This relationship was attributable to WASO, with both TD (r = 0.187) and eTRIMP (r = 0.179) having positive correlations with WASO. A positive correlation with session duration was observed for TD (r = 0.811), eTRIMP (r = 0.914), HSR (r = 0.417), and sRPE-TL (r = 0.168). Significant associations between workload, sleep, and wellness outcomes were found, with WASO and session duration emerging as key factors. Although we observed associations between workload, subjective wellness, sleep outcomes, the small-to-moderate relationship strengths suggest other contributing factors. Practitioners should prioritize sleep hygiene education to help athletes mitigate potential sleep disruptions caused by training.